Diverse disparities: The politics and economics of wage, market and disposable income inequalities - Pablo Beramendi; Thomas R. Cusack (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
This paper analyzes the evolution of inequality and its determinants across different forms of income. A number of results emerge from this effort. First, OECD countries have been and continue to be much more diverse in their distributions of earnings and disposable income than they are in their distributions of market income. Second, the larger cross-national variation in the distributions of earnings and disposable income can be attributed to the role of political actors (such as unions and, more importantly, political parties) and economic institutions that allow actors to coordinate their activities. Third, the transmission of cross-national differences in wage inequality into market-based inequality appears to be muted relative to economic and demographic transformations that have gone on within the OECD countries. Fourth, the way in which political parties are able to pursue their goals varies across forms of income. Political parties' capacity to shape the distribution of earnings is contingent on the degree of wage bargaining coordination. Absent coordination between labor and capital, right-wing policy works to modestly increase inequality. Alternatively, the egalitarian efforts of left-wing parties have the undesired effect of raising earnings inequality. In contrast, when labor market actors are able to coordinate, left-wing policy reinforces the egalitarian effects of coordination whereas the impact of right-wing policy is institutionally constrained. In turn, political parties affect directly the distribution of disposable income through their choices about fiscal redistribution. – – In diesem Papier werden die Entwicklungen und die Determinanten der Ungleichheit verschiedener Einkommensarten untersucht. Als erstes Ergebnis lässt sicht feststellen, dass zwischen den OECD-Ländern größere Unterschiede in der Verteilung von Lohneinkommen und verfügbarem Einkommen als in der Verteilung von Markteinkommen bestanden und weiterhin bestehen. Zweitens kann die größere Variation der Einkommensverteilung über die Länder bezüglich Lohneinkommen und verfügbarem Einkommen der Rolle politischer Akteure, wie Gewerkschaften oder, noch wichtiger, politische Parteien, zugeschrieben werden. Auch ökonomische Institutionen, durch die die Akteure ihre Handlungen koordinieren, spielen eine Rolle. Drittens wird die Übertragung von Unterschieden in der Lohnungleichheit auf marktbasierte Ungleichheit von den ökonomischen und demografischen Transformationen verdeckt, denen die OECD-Länder unterliegen. Viertens variiert die Art und Weise, wie politische Parteien ihre Ziele verfolgen können zwischen den Einkommensarten. Die Möglichkeit, die Verteilung des Lohneinkommens zu beeinflussen, hängt vom Grad der Koordination der Lohnverhandlungen ab. Fehlt eine Koordination zwischen den Tarifparteien auf dem Arbeitsmarkt, resultiert aus konservativer Politik ein leichter Anstieg der Ungleichheit. Noch stärker tritt der unerwünschte Effekt, Lohnungleichheit zu erhöhen, bei den egalitären Bemühungen der linken Parteien auf. Im Gegensatz dazu verstärken in einer Situation mit koordinierten Arbeitsmarktstrukturen linke Politikmaßnahmen den egalitären Effekt der Koordination, während der Wirkung der Politikmaßnahmen rechter Parteien institutionell ein Riegel vorgeschoben ist. Die Verteilung des verfügbaren Einkommens wiederum wird von den politischen Parteien direkt durch ihre Wahl der fiskalischen Umverteilung bestimmt.
Keywords: E62; I3; J31; J38; 330; Income Inequality; Partisan Politics; Institutions; Varieties of Capitalism; Redistribution